MODELING AND ANALYSIS OF CHISEL PLOUGH - Madhava, V.; Krishnudu, D Mohana; Hussain, P; Babu, Dr.S. Sudhakar (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The chisel plough is considered as a farm minimum tillage tool for leaving mulch remaining on the soil surface. The quantity of carbon dioxide that gets lost during tillage depends on the used implement; the disk harrow causes bigger loss than the chisel plough. The chisel plough has been introduced in Venezuela since 1973. The efficient performance of the chisel plough is function of the position of the bodies in the frame. The specific objectives consisted on relating the number, distances and position of the shank with the bulk density, water content, porosity, efficiency, field capacity, working depth, draft requirement, weed control and clod size. An 82 kW John Deere 4240 tractor was used, and a mounted chisel plough Bon ford Super flow standard model of 7 mobile chisel with a maximum working width of 2.44 m. A blocks design at random was used with eight treatments that consisted of varying the number, position and distance of the shanks with five repetitions. A conventional variance analysis was carried out among the eight treatments and the differences among them were detected by means of the Minimum Significant Difference Test with (p ≤ 0.05). It was obtained, the apparent density between 1.49 and 1.63 kg m3, the porosity between 32.59 and 37.78%; the depth between 24.86 and 28.80 cm, soil humidity between 10.63 and 14.58 cm3, the best weed control was for the position in V of five bodies, with 25 cm among bodies. On concluded, recommending the appropriate positional order of the bodies for the studied parameters, including weed residuals.